Challenges against Xi Jinping: an ASEAN Perspective - Abdullah Dahana; Kelly Rosalin (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2014)
Since the death of Mao Zedong in 1976 and Deng Xiaoping in 1997, factionalism and power struggle as the characteristic of leadership change in China has ended. Although factionalism still exists, it has been converted to collaboration among all factions within the Chinese Communist Party (CCP). The election of Xi Jinping to the presidency of the People’s Republic of China (PRC) and to the position as General Secretary of the Chinese Communist Party (CCP) is therefore, as the result of cooperation among factions. This paper discusses various challenges, including nationalism as the most serious issue faced by Xi Jinping as a leader elected through compromise.